2013
DOI: 10.1210/jc.2013-1381
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Profiling by Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS) in Healthy Normal-Weight Ovulatory and Anovulatory Late Adolescent and Young Women

Abstract: This is the first study providing LC-MS/MS-based, menstrual phase-specific reference intervals for the circulating androgen profile in young females. We identified a subgroup of anovulatory healthy females characterized by androgen imbalance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 38 publications
3
33
0
1
Order By: Relevance
“…The diagnosis of PCOS in adolescents is controversial, since anovulatory cycles can be observed even in the sixth year after menarche [50]. Moreover, normal menstruating girls often show elevated LH levels and androgen imbalance [51], suggesting predisposition to developing PCOS later in life. Thus, persistent oligomenorrhea, especially over 2 years beyond menarche, associated with hyperandrogenism can be considered a possible early sign of PCOS in adolescents [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of PCOS in adolescents is controversial, since anovulatory cycles can be observed even in the sixth year after menarche [50]. Moreover, normal menstruating girls often show elevated LH levels and androgen imbalance [51], suggesting predisposition to developing PCOS later in life. Thus, persistent oligomenorrhea, especially over 2 years beyond menarche, associated with hyperandrogenism can be considered a possible early sign of PCOS in adolescents [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that extremely accurate and sensitive technologies in the detection and analysis of steroids, such as liquid chromatography-tandem mass spectrometry (LC-MS/MS) (8), have significantly improved the definition of the androgenemic blood pattern in women with PCOS (11,12,13,14,15,16,17,18). These studies have clearly shown that a steroid profile, including not only testosterone blood levels but also androstenedione and the free androgen index (FAI), may optimize the diagnosis of hyperandrogemia in women with PCOS, therefore improving our understanding on the heterogeneity of its phenotypes.…”
Section: Arguments In Favor Of the Definition Of Secondary Pcosmentioning
confidence: 99%
“…In these girls, body mass index (BMI) may represent the best predictor of unbound testosterone levels, much more than luteinizing hormone (LH) and insulin levels, and the Tanner stage (27). Large population-based studies have also shown that half of oligomenorrheic girls may have significantly increased LH and androgen levels (28), although this finding still remains controversial, since other studies performed in healthy normal-weight girls with anovulatory regular menses showed that they were characterized by a significantly higher androgen levels in comparison with those with ovulatory menses (29). Intriguingly, longitudinal studies have shown that adolescent serum androgen levels may be preserved into adulthood and are associated with menstrual dysfunction, which suggests a potential risk to develop PCOS (30).…”
Section: Arguments In Favor Of the Definition Of Secondary Pcosmentioning
confidence: 99%
“…Distinction between normal, heterozygotes, non-classic and classic CAH forms by measuring 17-OHP after ACTH stimulation was first described by Maria New and then others 93,94 This has not been repeated with modern MS assays though basal reference ranges according to age and gender have been reported. 82,83,90 An equivalent chart for GC-MS analysis is shown in Figure 2 with results closer to LC-MS/ MS methods than IA methods. As a guide, 17-OHP after ACTH stimulation is >30 nmol/L (10 ng/mL) in NC-CAH.…”
Section: -Ohp Assay Performancementioning
confidence: 99%